CIAT in Africa: Science for Impact - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2017)
The International Center for Tropical Agriculture (CIAT), in collaboration with our national research partners, has been working in Africa for the last 30 years. Our cutting-edge science helps policy makers, private sector, scientists, civil society, and farmers respond to the most pressing challenges of our time. Our research draws on international expertise in various disciplines. Using the world’s largest collections of beans and livestock forages, we work to tackle poverty, food insecurity, gender inequality, malnutrition, climate change, and land and environmental degradation, contributing towards seven of the United Nations’ Sustainable Development Goals (SDGs).